Fusion spectrum sensing algorithm based on eigenvalues - Wenjing ZHAO; He LI; Minglu JIN (Tongxin xuebao)
Aiming at the problem of inefficient use of spectrum resources,a fusion spectrum sensing algorithm based on eigenvalues was proposed to effectively achieve dynamic spectrum sharing.The test statistics were constructed by employing the maximum eigenvalue,the trace and the geometric mean of all eigenvalues of the sample covariance matrix.The detection probability and false alarm probability of the proposed method were analyzed using the random matrix theory,and the analytical representation of the theoretical threshold was obtained.In addition,the parameter selection of the proposed algorithm was analyzed theoretically.Simulation results show that the proposed algorithm has better detection ability than the existing eigenvalue detection algorithm.